Beyond the lifetime of organizations: A framework for multi-generational goal survival in the ecology of goals. (March 2021) - Kurtz, Samuel A.
Highlights: There exists an ecology of goals through which goals compete with each other for survival under conditions of shock events. The completion of initiative often requires goal survival beyond the lifetime of individual organizations via inter-organizational adoption. The spectrum of organizations available to adopt goals is determined by capability, appropriateness, autonomy, as well as the interest and time horizon of decision makers. The orientation that decision makers have towards the future is critical for addressing existential threats to our species. Abstract: The completion of initiatives designed to address wicked problems often requires the participation of a variety of actors spanning multiple generations of both individuals and organizations. Until now, frameworks for addressing problems and articulating the sustainability of goals related to overcoming them have yet to adequately account for the timespans required for addressing such problems; particularly as far as the lifecycle of organizations is shorter than such timespans. Here, a framework is presented to articulate the survival of goals to the point of initiative completion under conditions in which it is not assumed that any individual organization or subunit exists long enough to fulfill the requirements for completing such initiatives.